2011
DOI: 10.5754/hge11516
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Screening Biomarker in Gastric Cancer: Serum Dickkopf-1

Abstract: Serum DKK-1 levels may be a potentially useful novel serologic marker for gastric cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 0 publications
0
23
0
2
Order By: Relevance
“…Than et al (81) reported that administration of adenovirus vector carrying REIC/DKK-3 (Ad-REIC/DKK-3) can inhibit scirrhous gastric carcinoma (SGC) both in vitro and in nude mice by boosting apoptosis and recruitment of NK cells. On the contrary, despite DKK-1 or DKK-3 being Wnt suppressors, these protein have been detected upregulated in GC as well as significantly correlated to pT-stage and UICC stage (82,83), revealing that DKKs could have potential in oncogenesis of gastric cancer rather than as tumor inactivators, which might be explained either as a negative feedback loop in response to initial Wnt/β-catenin signaling activation or mediation by non-canonical Wnt pathways (84). Shin et al (85) sought to assess the role of secreted frizzled-related proteins (SFRPs) as antagonist of Wnt pathway and confirmed that aber rant methylation of SFRPs is the major mechanism by which Wnt signaling is activated in human GC cells.…”
Section: Wnt/β-catenin Pathway and Gastric Cancermentioning
confidence: 99%
“…Than et al (81) reported that administration of adenovirus vector carrying REIC/DKK-3 (Ad-REIC/DKK-3) can inhibit scirrhous gastric carcinoma (SGC) both in vitro and in nude mice by boosting apoptosis and recruitment of NK cells. On the contrary, despite DKK-1 or DKK-3 being Wnt suppressors, these protein have been detected upregulated in GC as well as significantly correlated to pT-stage and UICC stage (82,83), revealing that DKKs could have potential in oncogenesis of gastric cancer rather than as tumor inactivators, which might be explained either as a negative feedback loop in response to initial Wnt/β-catenin signaling activation or mediation by non-canonical Wnt pathways (84). Shin et al (85) sought to assess the role of secreted frizzled-related proteins (SFRPs) as antagonist of Wnt pathway and confirmed that aber rant methylation of SFRPs is the major mechanism by which Wnt signaling is activated in human GC cells.…”
Section: Wnt/β-catenin Pathway and Gastric Cancermentioning
confidence: 99%
“…(Sato et al, 2010;Kemik et al, 2011;Gomceli et al, 2012;Jiang, Huang, Zhang, 2013;Yang et al, 2013).…”
Section: Discussionunclassified
“…Some studies have demonstrated over-expression of DKK-1 in patients with Wilms tumor, hepatoblastoma, hepatocellular carcinoma, gastric cancer, rectal cancer, colon cancer, gynecological cancers, indicating that DKK-1 has a latent oncogenic role in these tumors (Wirths et al, 2003;Patil et al, 2005;Jianget al, 2009;Kemik et al, 2011;Soydinc et al, 2011;Tung et al, 2011;Gomceli et al, 2012;Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms that control gastric cancer invasion and metastasis have not been clarified yet. The ability of gastric cancer cell invasion is related to mutations in both oncogenes and tumor suppressor genes, and is affected by growth factors, inflammatory cytokines and angiogenesis [50][51][52]. In addition, cancer cellular ROS may also play an important role in their invasion and metastasis [53,54] because ROS regulate activation of actin remodeling proteins and focal adhesion proteins [55,56].…”
Section: Reactive Oxygen Species and Invasion/metastasismentioning
confidence: 99%